Legal Capacity of Individuals with Bipolar Disorder in Islamic Marriage Law: Integrating Ahliyyah al-Adā’ and Maqāṣid al-Syarī‘ah - Syifa Arinda; Dinda Seplinar Batubara; Keisyah Yuvi Amanda; Abdul Latif; M. Rifky Abdillah; Icha Azdina Adly (Tabayyanu : Journal Of Islamic Law, 2024)
Marriage in Islamic law is founded upon the principles of legal capacity (ahliyyah), mutual consent, and the realization of maqāṣid al-sharī‘ah through the protection of religion, life, intellect, lineage, and property. Nevertheless, the increasing prevalence of bipolar disorder has generated complex legal and ethical questions regarding the legal capacity of affected individuals to enter into marriage and to perform the reciprocal rights and obligations arising from the marital contract. Existing scholarship has predominantly examined bipolar disorder from isolated perspectives, including marriage validity, child custody, or disability rights, without providing an integrated legal framework that reconciles classical Islamic jurisprudence, contemporary mental health knowledge, and Islamic family law. This study aims to reconstruct the concept of legal capacity for individuals with bipolar disorder in Islamic marriage law by integrating the doctrine of ahliyyah al-adā’ with the objectives of maqāṣid al-sharī‘ah. Employing normative juridical research, the study combines statutory, conceptual, comparative, and Islamic jurisprudential approaches. Primary legal materials consist of the Qur'an, Sunnah, classical fiqh literature, Indonesian marriage legislation, the Compilation of Islamic Law, and selected judicial decisions, while secondary materials include recent peer-reviewed international journals on Islamic family law, disability studies, and psychiatric research. The study demonstrates that bipolar disorder should not constitute an automatic legal impediment to marriage. Rather, legal capacity must be determined through an individualized assessment of cognitive competence, decisional autonomy, psychological stability at the time of the marriage contract, and the ability to fulfil marital obligations. The article proposes a reconstructed framework in which ahliyyah al-adā’ is interpreted dynamically through the lens of maqāṣid al-sharī‘ah, emphasizing transparency regarding mental health conditions, protection of both spouses, and proportional legal safeguards instead of categorical exclusion. This reconstruction contributes to contemporary Islamic family law by harmonizing classical jurisprudential doctrines with modern psychiatric knowledge and human rights principles while strengthening substantive justice in Muslim family law.